(untitled) (Scientific journal of the Fergana State University, 2025)
This paper presents scientific information on the formation of Cu15Si4 thin films on the surface of single-crystal silicon, their surface morphology and the mechanism of film formation. The formation mechanism of metal and silicide nanofilms using different modes of magnetron sputtering is explained. The film thickness was measured using SEM. The elemental composition was determined by energy-dispersive spectroscopy. The surface morphology was investigated using a laser confocal microscope. The electrical properties were determined using SBA-458. The optical properties were analyzed using an IR spectrophotometer. The formation of copper silicide (Cu) film depends on the copper crystal size and substrate temperature, and at 467oC, 75 nm thick Cu15Si4 film was formed under 130 nm thick copper layer. This study demonstrated the potential of using copper sputtered silicon to improve the performance of metal-oxide-semiconductor transistors and high-speed integrated circuits (IS).